2008
DOI: 10.1097/fpc.0b013e3282fad38a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of epitestosterone formation and androgen disposition: influence of polymorphisms in CYP17 and UGT2B enzymes

Abstract: The CYP17 promoter polymorphism may partly explain high natural (>4) T/E ratios. Our data indicate that 5-androstene-3beta, 17alpha-diol is an important precursor of epitestosterone and that CYP17 is involved in its production. In addition, we found that lack of the UGT2B17 enzyme may be compensated for by increase in UGT2B15 transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 39 publications
11
42
0
1
Order By: Relevance
“…We have demonstrated that a common deletion polymorphism in the gene coding for uridine diphosphate-glucuronosyltranferase (UGT) 2B17 (11) is strongly associated with testosterone glucuronide levels in urine (4) and that 40% of the individuals lacking the UGT2B17 gene would never reach the cutoff ratio of 4.0 used today after a single dose of 360 mg testosterone (6). We have also shown that a thymine greater than a thymine/cytosine (A1/A2) promoter polymorphism in the CYP17 gene is associated with lower urinary epitestosterone excretion resulting in 64% higher T/E ratios in homozygotes, increasing the risk of false-positive doping test results (12). Sottas et al (reviewed in Ref.…”
mentioning
confidence: 87%
“…We have demonstrated that a common deletion polymorphism in the gene coding for uridine diphosphate-glucuronosyltranferase (UGT) 2B17 (11) is strongly associated with testosterone glucuronide levels in urine (4) and that 40% of the individuals lacking the UGT2B17 gene would never reach the cutoff ratio of 4.0 used today after a single dose of 360 mg testosterone (6). We have also shown that a thymine greater than a thymine/cytosine (A1/A2) promoter polymorphism in the CYP17 gene is associated with lower urinary epitestosterone excretion resulting in 64% higher T/E ratios in homozygotes, increasing the risk of false-positive doping test results (12). Sottas et al (reviewed in Ref.…”
mentioning
confidence: 87%
“…There are also individuals that have naturally high T/E ratios due to decreased excretion of epitestosterone. In males, part of this low epitestosterone excretion can be explained by a promoter polymorphism in the CYP17 gene (13), resulting in 64% higher T/E ratios in men homozygous for the T allele (14). However, this polymorphism in relation to epitestosterone excretion has not been studied in women.…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of UGT2B17 deletion polymorphism was performed using real-time PCR as described previously (Schulze et al, 2008).…”
Section: Methodsmentioning
confidence: 99%